MECHANISMS FOR FORMING FINANCIAL RESOURCES OF TERRITORIAL COMMUNITIES UNDER DECENTRALIZATION CONDITIONS - Goncharenko M.V. (Pressing Problems of Public Administration, 2017)
The paper is devoted to investigation of the existing mechanisms for forming  nancial resources oflocal governments and determining extra opportunities for  nancial support of associated territorialcommunities in the context of the decentralization reform.